Parents’ perspectives on a national child oral health promotion program: Sociodemographic influences and behavioral insights – A cross-sectional analysis - Mohammad Reza Khami; Mohammadreza Naderi; Shabnam Varmazyari (PLoS ONE, 2026)
Background Iran’s Students’ Oral Health Promotion Program (SOHPP) aimed to improve primary school children’s oral health, but parental perceptions of this program, as key stakeholders, remain underexplored. This study explores parents’ perceptions of Iran’s SOHPP, the sociodemographic factors shaping them, and children’s post-program oral health behaviors. Methods Conducted at four randomly-selected comprehensive healthcare centers in Tehran (July–August 2020), this cross-sectional study phone-surveyed parents of primary school children who participated in Iran’s SOHPP. The questionnaire covered sociodemographics, children’s post-program oral health behaviors, and awareness and satisfaction with key SOHPP components: oral health education, fluoride therapy, electronic oral health profiling, and treatment need identification. ANOVA, chi-square, and regression models served for statistical analysis. Results The 354 surveyed parents (response rate: 67%), on average, scored 79% for SOHPP awareness and 74% for satisfaction. Awareness and satisfaction were lowest for treatment-related components (58.2% and 52.0% for oral health profiling; 70.9% and 53.7% for treatment need identification). Fluoride therapy acceptance was 76.6%, with refusals mainly due to poor notification and limited procedural understanding. While 61.6% of parents noted improved tooth-brushing in their child, post-program, only 38.7% reported twice-daily brushing, and 37.9% were unaware of their fluoride toothpaste use. Additionally, 41.5% reported sugary snacking at least once daily by their child, while 83.0% reported healthy school food intake. More educated fathers had greater program awareness (B = 0.18, p = 0.040), satisfaction (B = 0.17, p = 0.032), and fluoride therapy acceptance (OR = 1.37, p = 0.024), whereas government-employed household heads were less aware (B = –1.16, p = 0.004) and less likely to perceive tooth-brushing improvements (B = –1.48, p = 0.001). Conclusions To improve parents’ perceptions of Iran’s SOHPP, enhanced delivery of treatment-related components, improved fluoride therapy transparency, reinforced post-program oral health behaviors, and tailored outreach to fathers’ education and household heads’ government employment are recommended.